Biologically active secondary metabolites from white-rot fungi - Pinar, Orkun; Rodríguez-Couto, Susana (Frontiers in Chemistry, 2024)
In recent years, there has been a considerable rise in the production of novel metabolites derived from fungi compared to the ones originating from bacteria. These organic substances are utilized in various sectors such as farming, healthcare, and pharmaceutical. Since all dividing living cells contain primary metabolites, secondary metabolites are synthesized by utilizing intermediate compounds or by-products generated from the primary metabolic pathways. Secondary metabolites are not critical for the growth and development of an organism; however, they exhibit a variety of distinct biological characteristics. White-rot fungi are the only microorganisms able to decompose all wood components. Hence, they play an important role in both the carbon and nitrogen cycles by decomposing non-living organic substrates. They are ubiquitous in nature, particularly in hardwood (e.g., birch and aspen) forests. White-rot fungi, besides ligninolytic enzymes, produce different bioactive substances during their secondary metabolism including some compounds with antimicrobial and anticancer properties. Such properties could be of potential interest for the pharmaceutical industries. Considering the importance of the untapped biologically active secondary metabolites from white-rot fungi, the present paper reviews the secondary metabolites produced by white-rot fungi with different interesting bioactivities.